Food safety concerns and consumer preferences for food safety attributes: Evidence from China. (June 2020) - Liu, Ruifeng; Gao, Zhifeng; Snell, Heather Arielle; Ma, Hengyun
Abstract: China has experienced a series of high-profile food safety scandals in the past few years that seriously challenged public confidence in the domestic food industry. Much attention has been paid to Chinese government's food regulatory and inspection systems. Scant research, however, has been devoted to analyzing Chinese consumers' food safety concerns. This study interviewed 2092 Chinese consumers in Beijing, Shanghai, Guangzhou, Xi'an, Jinan, and Harbin and used the Conditional Logit model, Mixed Logit model, and the Latent Class model to analyze consumer preferences and marginal willingness to pay (WTP) for selected food safety attributes of Fuji apple products. We identified three consumer segments: certification-oriented (65.9%), price and origin-oriented (19.1%), and not interested (15.0%). Results reveal that Chinese consumers, in general, are willing to pay a premium for selected food safety attributes. Consumers' perceptual and attitudinal factors and socio-demographic characteristics are used to determine the sources of preference heterogeneity. Marginal analysis is also conducted to estimate the response of the model and selectione'd probability to potential policy levels, such as increasing the perception of food safety and the trust on labeling and traceability information to improve the evaluation of food safety. Highlights: Conduct a discrete choice experiment in five cities across China. Identify three consumer segments but most consumers are certification-oriented. Find consumers valuate the government certification most. Conclude region of origin and price are major attributes of consumer choices. Suggest simplifying labeling application and specific information program.